Integrated biomechanical diagnostic procedures in athletes` training - Coh, M. (Homosporticus, 2009)
The sports results at the current level of development of technology and sport training methodology are a result of a planned, programmed and controlled process of sports training. This is an extremely complex process that has to have predefined goals, resources and training methods. Diagnostics based on new methods has a function of immense importance in the structure of modern sports training. The purpose of diagnostic procedures is gathering of relevant and objective parameters for the preparation of athletes. Biomechanical laboratories operate today based on the principle of integration and synchronization of diagnostic measuring instruments and methods. Interrelated systems enable us to conduct complex analyses of biomotoric capabilities and control of movement structures. Such a strategy of biomechanical research enables us to establish quantity and quality characteristics of the preparation of athletes. Based on data gathered in such a way, the best resources are selected, and a division into cycles and modeling of trainings is conducted. This paper includes some biomechanical diagnostic methods, including kinematics, dynamics, electromyography and isokinetics. All these methods have been successfully implemented in the process of training and diagnostics of athletes who achieved the best international sports results.